Interrogating the Effectiveness of Educational Practices: A Critique of Evidence-Based Psychosocial Treatments for Children Diagnosed with Attention-Deficit/Hyperactivity Disorder - Koutsoklenis, Athanasios; Gaitanidis, Anastasios (Frontiers in Education, 2017)
In this paper we critically evaluate the literature of evidence–based psychosocial interventions for children diagnosed with ADHD. Our paper is structured around five main criticisms. First, the evidence–based psychosocial interventions are formulated on the basis of the categorical diagnosis of ADHD which is an ambiguous diagnostic entity. Second, they claim homogeneity among children diagnosed with ADHD. Third, they diffuse non–pedagogical language in education. The fourth criticism refers to the methodological bias by which evidence is produced. The fifth and final criticism describes how this body of literature promotes a pedagogical practice that relies on manualized approaches to be considered effective.